1978
DOI: 10.1002/qua.560130402
|View full text |Cite
|
Sign up to set email alerts
|

Ab initioLCAOMOSCF calculation of the electrostatic molecular potential of chlorpromazine and promazine

Abstract: AbstractsThe electrostatic potential V(r) arising from the ab initio LCAO-MO-SCF wave functions of chlorpromazine ( c p z ) and promazine (PZ) has been calculated and discussed. In this approximation, the most probable sites of attack and reaction paths of electrophilic reagents are pointed out and compared. The analysis of V(r) shows that the phenothiazine group has strong nucleophilic properties which are influenced by the phenothiazine substituent and that the electrostatic reactivity of CPZ and PZ is decid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…tions give relatively good results (first-order accuracy) for properties that are calculated from the electronic density function, as is V(rT) (5-7). Furthermore, extensive investigations have shown that a generally reliable electrostatic potential can be obtained even with self-consistent-field (SCF) wave functions that are not near Hartree-Fock quality (1,(8)(9)(10)(11)(12)(13). V(Fr) is also being determined experimentally to an increasing extent, by diffraction methods (14)(15)(16)(17), but at present the quantum chemical approach remains the more accurate and more practical one.…”
mentioning
confidence: 99%
“…tions give relatively good results (first-order accuracy) for properties that are calculated from the electronic density function, as is V(rT) (5-7). Furthermore, extensive investigations have shown that a generally reliable electrostatic potential can be obtained even with self-consistent-field (SCF) wave functions that are not near Hartree-Fock quality (1,(8)(9)(10)(11)(12)(13). V(Fr) is also being determined experimentally to an increasing extent, by diffraction methods (14)(15)(16)(17), but at present the quantum chemical approach remains the more accurate and more practical one.…”
mentioning
confidence: 99%
“…In the rr-region of the ally1 group, only the semiempirical results using the approximation IV and the s~o -6 G expansion are in agreement with the ab initio ones. From these and other results [55,58,61,62] the conclusion remains that the CNDO and INDO methods can only be used with caution to get V(r) and that it seems difficult to derive any general rules.…”
Section: And Indo Eigenvectors Different Expansions S T O -~G or S mentioning
confidence: 84%
“…The case of requirement of similar maps around the pharmacophoric portions of direct agonists to normal neurotransmitters and the normal neurotransmitters themselves or around the relevant pharmacophoric portions of two related drugs with the same mode of direct action is more stringent than requirements on maps for comparison of agonist and antagonist action. Moreover, to investigate in a thorough and comprehensive manner, the agreement or disagreement of electrostatic molecular potential maps generated from CNDO or INDO wave functions (either orthogonalized or deorthogonalized), to determine the influence of the various approximations when CNDO or INDO wave functions are used and to assess the influence of the GTO expansion to STOS in collaboration with Petronogolo [61] we generated the maps using both approximations I11 and IV and s~o -3 G and s~o -6 G expansions. Striking changes are obtained deorthogonalizing both the CNDO …”
Section: B Electrostatic Molecular Potential Contour Mapsmentioning
confidence: 99%
“…Using the criterion we defined above, that two related drugs which exert a common pharmacological effect must generate similar or identical maps around their relevant pharmacologically significant pharmacophores, it was seen that around the N atom in the lone-pair direction relative to the N atom in the morphine and nalorphine molecules, the electrostatic molecular potential contour maps were generated that were almost identical in shape as well as numerical value [41]. Thus, it must be in this direction from the N atom that both the morphine and nalorphine exert their common narcotic agonist effect.…”
Section: B Electrostatic Molecular Potential Contour Mapsmentioning
confidence: 99%